Nitrate Ions’ Influence on the Alloy 22 Corrosion Behavior (2015)
Alloy 22 (N06022), is a nickel based alloy, with a high content of chromium (∼22%) and molybdenum (∼13%) that belongs to the Ni-Cr-Mo alloys family. Different studies show that the alloy 22 is resistant to generalized and localized (in crevices) corrosion in aqueous solution, with high chloride concentration, and in a wide range of temperatures.Electrochemical techniques such as Electrochemical Impedance Spectroscopy (EIS) and PotentiodynamicGalvanostatic-Potentiodynamic (PD-GS-PD) and non-electrochemical techniques such as the Scanning Electron Microscopy (SEM), were applied to determine the effect of the ionic nitrates and chlorides upon the alloy 22 at 90 oC generalized and localized corrosion.The results show that for a critical molar concentration ratio R= [NO3 -]/ [Cl-] ≥0.2 it is completely eliminated the alloy 22 susceptibility to the crevice corrosion. The corrosion speed rates obtained were about 0.1μm/year at 24 hours of immersion.